2004
DOI: 10.1210/jc.2003-031244
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Placental Growth Factor and Soluble Fms-Like Tyrosine Kinase 1 and Risk for Preeclampsia

Abstract: An imbalance of pro- and antiangiogenic factors may lead to preeclampsia (PE). In this prospective nested case-control study, we investigated whether first trimester serum levels of placental growth factor (PlGF), a potent angiogenic factor, and its soluble inhibitor, soluble fms-like tyrosine kinase 1 (sFlt1), distinguished women who developed PE (n = 40) from those who developed gestational hypertension (n = 40), delivered a small for gestational age (SGA) newborn (n = 40), or completed a full term normal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
300
1
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 411 publications
(331 citation statements)
references
References 53 publications
17
300
1
13
Order By: Relevance
“…19 The undetectable levels of VEGF and PlGF in the pregnant rats in the current study were in agreement with other investigators, who failed to detect these angiogenic factors in a large population of pregnant women regardless of the end result of pregnancy. [20][21][22] Furthermore, low PlGF in the presence of high sFlt-1 levels, as observed in the PRE group in the current study, increased the risk of PE in a prospective nested control study. 21 The decrease in circulating VEGF and PlGF in PE could be due to decreased placental production.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…19 The undetectable levels of VEGF and PlGF in the pregnant rats in the current study were in agreement with other investigators, who failed to detect these angiogenic factors in a large population of pregnant women regardless of the end result of pregnancy. [20][21][22] Furthermore, low PlGF in the presence of high sFlt-1 levels, as observed in the PRE group in the current study, increased the risk of PE in a prospective nested control study. 21 The decrease in circulating VEGF and PlGF in PE could be due to decreased placental production.…”
Section: Discussionsupporting
confidence: 66%
“…[20][21][22] Furthermore, low PlGF in the presence of high sFlt-1 levels, as observed in the PRE group in the current study, increased the risk of PE in a prospective nested control study. 21 The decrease in circulating VEGF and PlGF in PE could be due to decreased placental production. 23 Moreover, increased sFlt-1 is suggested to bind to these angiogenic factors and decrease their free fractions.…”
Section: Discussionsupporting
confidence: 66%
“…In agreement with the existing literature on early pregnancy, [23][24][25][26][27] we found that low levels of PiGF at 10-15 weeks of gestation predict the subsequent development of pre-eclampsia. However, we found no significant link between sFlt-1 or sEng and pre-eclampsia during this gestational period, in keeping with the results from other authors.…”
Section: Discussionsupporting
confidence: 92%
“…However, we found no significant link between sFlt-1 or sEng and pre-eclampsia during this gestational period, in keeping with the results from other authors. 3,[23][24][25]28 It would appear that women who develop pre-eclampsia begin to show higher levels of sFlt-1 and sEng only well into the second trimester of pregnancy. 2,3,28 In contrast, elevations of Bb occur much earlier.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, low levels of PlGF have been associated with pre-eclampsia (25)(26)(27)(28)(29)(30), and endometrial PlGF is reported to be an exclusive product of uNK cells in the late menstrual cycle. PlGF is also found in uNK cells from early, elective pregnancy terminations (5).…”
Section: Discussionmentioning
confidence: 99%